Case report: A novel c.1842_1845dup mutation of ETFDH in two Chinese siblings with multiple acyl-CoA dehydrogenase deficiency - Yuan, Gaopin; Zhang, Xiaohong; Chen, Tingli; Lin, Jiansheng (Frontiers in Pediatrics, 2023)
This article reports the characterization of two siblings diagnosed with late-onset multiple Acyl-CoA dehydrogenase deficiency (MADD) caused by mutations in electron transfer flavoprotein(ETF)-ubiquinone oxidoreductase (ETF-QO) (ETFDH) gene. Whole exome sequencing (WES) was performed in the proband's pedigree. Clinical phenotypes of Proband 1 (acidosis, hypoglycemia, hypotonia, muscle weakness, vomiting, hypoglycemia, hepatomegaly, glutaric acidemia, and glutaric aciduria) were consistent with symptoms of MADD caused by the ETFDH mutation. However, Proband 2 presented with only a short stature. The patients (exhibiting Probands 1 and 2) showed identical elevations of C6, C8, C10, C12, and C14:1. c.1842_1845(exon13)dup, and c.250(exon3) G>A of the ETFDH gene were compound heterozygous variants in both patients. The novel variant c.1842_1845dup was rated as likely pathogenic according to the American College of Medical Genetics and Genomics guidelines (ACMG). This is the first report on the c.1842_1845dup mutation of the ETFDH gene in patients with late-onset MADD, and the data described herein may help expand the mutation spectrum of ETFDH.